2015
DOI: 10.21863/atithya/2015.1.1.007
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Benefits of Convenience Foods to Working Women

Abstract: The last decade and half has seen a remarkable growth in the working women segment in India and so has the manufacture of convenience food industry grown in the last decade. The working women in India who today are not only just seeking jobs but also are career oriented. Apart from their jobs, career, meetings and targets they are also a part of a family where a working woman needs to care of their meals too. This study aims at finding out about the use of convenience food by working women and of their need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It could be suggested that, when people are more engaged in purchasing street foods voluntarily, their own attitude towards this behavior would be significant as well [104]. Contradicting with other studies [31][32][33][34][35]76], it could be deduced that behavioral intention on purchasing intentions in the Philippines is only based on their control, rather than other behavioral aspects. This means that the people in the Philippines are purchasing street foods based on choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be suggested that, when people are more engaged in purchasing street foods voluntarily, their own attitude towards this behavior would be significant as well [104]. Contradicting with other studies [31][32][33][34][35]76], it could be deduced that behavioral intention on purchasing intentions in the Philippines is only based on their control, rather than other behavioral aspects. This means that the people in the Philippines are purchasing street foods based on choice.…”
Section: Discussionmentioning
confidence: 99%
“…Plasek et al [77] added that sensory perceptions among consumers affects their consumption of street foods, as these reflect the value of the foods being considered. These perceptions affect an individual's behavior in terms of consumption [31][32][33][34][35]. The different studies presented how PFV may affect the behavioral domains of consumers; therefore, the following were hypothesized:…”
Section: H2mentioning
confidence: 99%
See 1 more Smart Citation
“…Srinivasan and Shende [25] stated that about 81% of women used these foods due to the unavailability of food ingredients, while around 70% of women did not know the preparation of a recipe. It was found that even non-working women were not left far behind in selecting such products for their families.…”
Section: Attributes Affecting the Consumption Of Convenience Foodmentioning
confidence: 99%
“…The nutritional profile of the best treatment (P2) shows that the product, besides being energy dense is excellent source of nutrients and will cater to the need of both gluten sensitive and other population. foods as well (Sehgal et al, 2010;Srinivasan and Shende, 2015). According to (Parameswaran, 2019) the revenue in the snack food segment amounts to over $ 5,000 million in 2019 and the market is expected to grow annually by 7.5 % (CAGR 2019(CAGR -2023.…”
Section: Introductionmentioning
confidence: 99%